Behring Sea arbitration [electronic resource] : indexes to the British case, counter-case, and argument, and to the report of the Behring Sea Commission, and report of the Behring Sea commissioners. - Bering Sea Tribunal of Arbitration. ([London? : s.n., 1893)
Electronic reproduction. Mode of access: Internet. 44